Assessment of factors influencing visitation to rodent management devices at food distribution centers. (September 2021) - Frye, Matthew J.; Gangloff-Kaufmann, Jody L.; Corrigan, Robert M.; Hirsch, Hank; Bondy, Dusana
Abstract: Rodent management programs at food distribution centers in the United States and Canada often adhere to interval-based spacing of control devices, with traps spaced 6–12 m apart on the interior perimeter, and exterior bait stations spaced 15–30 m apart. However, this design is based only on rodent foraging ranges, and does not consider the influence of rodent behavior or biology on movement patterns. Therefore, this study evaluated characteristics of food distribution centers that influence rodent behavior to determine their impact on interior trap capture and exterior bait feeding by rodents. We found that rodent interactions with control devices was not uniform in facilities, and less than half (45.2%) of all interior devices trapped at least one mouse. Rodent feeding at exterior bait stations was similarly not uniform, with 56.1% of observations representing minor feeding (one corner of bait or less consumed). Furthermore, we found that certain ecological and structural characteristics of device location were associated with higher trap capture and/or bait consumption. Results of this investigation suggest that rodent management at food distribution centers can be improved with assessment-based placement of traps and bait stations. In addition to reducing food safety threats through improved trap capture, this approach can reduce the number of devices to service and redirect service time toward pro-active inspections, rather than trap checking. Finally, device locations that are assessment-based align with the 2011 Food Safety Modernization Act that mandates preventive controls to protect human food. Highlights: Traps placed near attractive ecological & structural features had higher capture Exterior bait stations near attractive features had higher bait consumption Assessment-based placement of rodent traps and bait stations can improve management